2018
DOI: 10.1002/slct.201703126
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the Structure of Trans‐Cyclic Azobenzene by X‐Ray Crystallography and Spectroscopic Characterization of Cyclic Azobenzene Analogs

Abstract: The photoisomerization properties of a series of cyclic azobenzene (cAb) analogs, including non-substituted, Br-, CN-, carboxyl-, and amino cAb, were compared. While the transform of these analogs show different degrees of thermal stability, no spectral changes in the absorption wavelengths were observed for amino cAb upon exposure to purple light. The 15 N NMR chemical shifts of cAb in both cis-and trans-forms were found to show a large difference from those of aromatic azobenzene; however, the trend of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
(26 reference statements)
0
17
0
Order By: Relevance
“…In contrast to linear azobenzene, the ( Z ) isomer of cAB is thermodynamically favored over the ( E ) isomer by 37.08 kJ/mol . The switching behavior of cAB has been examined in detail by quantummechanical simulations , and spectroscopic methods. , However, compared to linear azobenzenes, diazocines have been used to a much lesser extent (examples are a photocontrolled switch in a peptide, in polyurea, on molecular platforms, and in oligonucleotides) . The reason for this low level of exploitation of these favorable properties is that although syntheses exist, they tend to be low yielding and substrate specific.…”
mentioning
confidence: 99%
“…In contrast to linear azobenzene, the ( Z ) isomer of cAB is thermodynamically favored over the ( E ) isomer by 37.08 kJ/mol . The switching behavior of cAB has been examined in detail by quantummechanical simulations , and spectroscopic methods. , However, compared to linear azobenzenes, diazocines have been used to a much lesser extent (examples are a photocontrolled switch in a peptide, in polyurea, on molecular platforms, and in oligonucleotides) . The reason for this low level of exploitation of these favorable properties is that although syntheses exist, they tend to be low yielding and substrate specific.…”
mentioning
confidence: 99%
“…It was reported that the eight‐membered diazocine systems are thermodynamically stable in the cis conformation . We have demonstrated that the effect of ring strain responsible for the stability of cis form does not extend to the 9‐membered ring system, as our system was found to be more stable in the trans form …”
Section: Resultsmentioning
confidence: 56%
“…[48,49] It was reported that the eight-memberedd iazocine systems are thermodynamically stable in the cis conformation. [50,51] We have demonstrated thatt he effect of ring strain responsible for the stability of cis form does not extendt ot he 9-membered ring system,a so ur system was found to be more stable in the trans form. [52] The effect of metal ions on the photoisomerization of azobenzene systems weres tudied in aA g I -complex with a2 4membered cyclic azobenzene by Ta maoki( Figure 1A) [43] where the trans-complex was found to be more stable.…”
Section: Resultsmentioning
confidence: 88%
“…69b Furthermore, the coupling of benzophenone imine with bromodiazocines was reported (Scheme 28, B). 71 The synthesis of a diazocine with turn-on fluorescence was achieved by the coupling of 3,8-dibromodiazocine with diphenylamine (Scheme 28, C). 72 Scheme 28 Buchwald-Hartwig cross-coupling reactions of diazocine derivatives 69b, 71,72 Turn-on fluorescence diazocines were prepared by a Stille cross-coupling reaction (Scheme 29, A).…”
Section: Scheme 27 Pd-catalyzed Heck Coupling Of Diazocine Derivativementioning
confidence: 99%
“…71 The synthesis of a diazocine with turn-on fluorescence was achieved by the coupling of 3,8-dibromodiazocine with diphenylamine (Scheme 28, C). 72 Scheme 28 Buchwald-Hartwig cross-coupling reactions of diazocine derivatives 69b, 71,72 Turn-on fluorescence diazocines were prepared by a Stille cross-coupling reaction (Scheme 29, A). 72 Furthermore, it was possible to obtain a pyroglutamate diazocine derivative via the Stille cross-coupling reaction (Scheme 29, B).…”
Section: Scheme 27 Pd-catalyzed Heck Coupling Of Diazocine Derivativementioning
confidence: 99%